Semen Evaluation, Preparation of Bangkok Roosters, and Insemination to Indonesian Native Hens - Asnawi; Maskur; Adji Santoso Dradjat; Muhammad Muhsinin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The success of artificial insemination in chickens is very dependent on sperm quality. Sperm temperature and diluent during storage can affect sperm quality. This study evaluated the quality of Bangkok chicken sperm diluted with 5% glucose and NaCl stored at 5 ⁰C and 26 ⁰C. The research design used was completely randomized. The data obtained were analyzed using a variance. The results showed that the motility of sperm preserved for 9 hours at 26 ⁰C with infused NaCl and Glucose 5% differed significantly (P< 0.05) with motility of 50±0.0% and 34±8.94%, respectively. While preservation under 5 ⁰C for 9 hours with NaCl, better than Glucose 5% (P<0.05) with motility of 58.00±10.95% and 38.00±10.95%, respectively. The viability of sperm preserved at 26 ⁰C with glucose 5% extender was better than NaCl (P<0.05) with a value of 58.93±1.27% and 33.43±1.27%, respectively. While preservation at 5 ⁰C of viabilities of sperm under Glucose 10% and NaCl were not significantly different (P>0.05) from values of 52.57±5.15% and 48.14±8.09%, respectively. The abnormality of sperm stored at 26 ⁰C and 5 ⁰C for 9 hours with NaCl and Glucose 5% were not different (P>0.05). Insemination using 100 million sperm with infused NaCl extender from 18 eggs produced 94.44% (n=17) fertility and 72.22% (n=13) hatchability. While insemination using infuse glucose 5% extender, 11 eggs produced 63.64% (n=7) fertility and 54.54% (n=6) hatchability. The infusing NaCl extender produced better sperm quality, fertility, and hatchability than glucose 5% at 5 ⁰C.